2018
DOI: 10.1111/jch.13153
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sacubitril/valsartan in patients with essential hypertension uncontrolled by olmesartan: A randomized, double‐blind, 8‐week study

Abstract: A majority of patients with hypertension fail to achieve blood pressure ( The overall incidence of adverse events was comparable between the groups.Compared with continued olmesartan, sacubitril/valsartan was more effective and generally safe in patients with hypertension uncontrolled with olmesartan 20 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 30 publications
0
58
0
5
Order By: Relevance
“…Сакубитрил/валсартан показва превъзходство по отношение на понижаване както на 24 часа амбулаторно измереното систолно АН, така и на офисното систолно АН от изходното за срок от 8 седмици в сравнение с олмесартан. Честотата на странични нежелани ефекти е сходна в двете групи с преобладване основно на главоболие и главозамайване [15]. Проучването на Supasyndh и кол.…”
Section: An Antihypertensive Eff Ect Of Sacubitril/ Valsartan (Entresto)unclassified
“…Сакубитрил/валсартан показва превъзходство по отношение на понижаване както на 24 часа амбулаторно измереното систолно АН, така и на офисното систолно АН от изходното за срок от 8 седмици в сравнение с олмесартан. Честотата на странични нежелани ефекти е сходна в двете групи с преобладване основно на главоболие и главозамайване [15]. Проучването на Supasyndh и кол.…”
Section: An Antihypertensive Eff Ect Of Sacubitril/ Valsartan (Entresto)unclassified
“…Numerous studies have demonstrated beneficial effects of sacubitril/valsartan on BP in patients without HF who have HTN ( Table 1 ). 11 21 The BP lowering effects of sacubitril/valsartan in patients with HTN has been evaluated both alone and in combination with other antihypertensive agents. The most recently published study on this topic by Cheung and colleagues evaluated 376 patients (mean age at baseline 57.6 years old) with an SBP ≥145 mmHg and <180 mmHg (mean baseline SBP was 157.5±9.85 mmHg and mean baseline 24-hour ambulatory SBP was 139.1±14.30 mmHg) who received either sacubitril/valsartan 200 mg orally once daily or olmesartan 20 mg orally once daily.…”
Section: Safety and Efficacy Of Blood Pressure Lowering With Sacubitrmentioning
confidence: 99%
“…Adverse event rates between groups were similar (23.4 versus 21.9%, respectively), with headache and dizziness being those most commonly reported. 11 A similar study by Supasyndh et al also evaluated the BP-lowering effects of sacubitril/valsartan 200 mg orally once daily (N=296) compared with olmesartan 20 mg orally once daily (N=292) over 14 weeks, albeit in an older population (mean age at baseline 70.7 years old). At week 10 of 14, patients with BP >140/90 mmHg had their antihypertensive doses up-titrated to sacubitril/valsartan 400 mg orally daily or olmesartan 40 mg orally daily, respectively.…”
Section: Safety and Efficacy Of Blood Pressure Lowering With Sacubitrmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this feature of sacubitril/valsartan may be an advantage in the treatment of hypertension. Compatible with this view, several studies investigated the potential of sacubitril/valsartan in hypertension treatment and found positive results ( 131 - 133 ). Sacubitril/valsartan decreased BP significantly and was found to be superior compared to ARBs, especially in elderly patients with arterial stiffness ( 133 , 134 ).…”
Section: Introductionmentioning
confidence: 99%